Dynamic Alterations of Oral Microbiota Related to Halitosis in Preschool Children - Zhang, Yu; Zhu, Ce; Cao, Guizhi; Zhan, Jingyu; Feng, Xiping; Chen, Xi (Frontiers in Cellular and Infection Microbiology, 2021)
Objective: This longitudinal study was aimed to evaluate the dynamic shift in oral microbiota during the process of halitosis progression among preschool children. Methods: The oral examinations, questionnaires and tongue coating specimens were collected at the baseline and 12-month follow-up. All children were oral healthy at the enrollment. At the 12-month follow-up, children who developed halitosis were included to the halitosis group (n=10). While children who matched the age, gender, kindergarten and without halitosis were included to the control group (n=10). 16S rRNA gene sequencing was used to reveal the shift of the tongue coating microbiome in these children during the 12- month period with the Human Oral Microbiome Database. Results: A remarkable shift in relative abundance of specific bacteria was observed prior to halitosis development. The principal coordinates and alpha diversity analyses revealed different shifting patterns of halitosis and the healthy participants’ microbiome structures and bacterial diversity over the 12-month follow-up. Both groups showed variable microbiota community structures before the onset of halitosis. Halitosis-enriched species Prevotella melaninogenica, Actinomyces sp._HMT_180 and Saccharibacteria TM7_G-1_bacterium_HMT_352 were finally selected as biomarkers in the halitosis-onset prediction model after screening, with a prediction accuracy of 91.7%. Conclusions: The microbiome composition and relative abundance of the tongue coatings in the halitosis and control groups remarkably differed, even prior to the onset of the clinical manifestations of halitosis. The halitosis prediction model constructed on the basis of tongue coating microbiome biomarkers indicated the microbial shifts before the halitosis onset. Therefore, this can be considered for the timely detection and intervention of halitosis in children.